(3GdeMbb ef Yde GdCUhd ajeG jJYdb HCaYGd GdQShds - (3CHh TGeI YHO GdQMef Hf ESeGYjd GdOeTbj,J (B665 (3g` s ((3EHQGgje Hf OGhO Hf XGaQ GdTGaYi GdYSbdGfi s)
(3ChdgG (B:s
(3GdCOdI GdeXgQI dCMcGe GdTQY YfO GdCFeI GdeYJHQjf GdbQBf hGdSfI hGdELeGY hGdbjGS hRGO HYV GdeUfajf GdESJOdGd s
(3BNQgG (B:s
(3hCbhd MbjbI GdChd Gfg ef HGH JYGQV Gdbhd hGdJbQjQ dG JYGQV Gdbhd hGdaYd abO Cecf GdLeY hdG JYGQV hGddg CYde hgh MSHfG hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1616s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs